Cell fate acquisition at a de novo developmental boundary in the maize leaf - Lukas J. Evans; Ruqiang Zhang; Maria Camila Medina; Elizabeth A. Fitzgerald; Anne W. Sylvester; George Chuck; Samuel Leiboff; Michael J. Scanlon (Proceedings of the National Academy of Sciences, 2026)
The formation of boundaries separating developmental fields with distinct gene expression and cell fate trajectories is a universal feature of noncolonial multicellular organisms. Developmental boundaries arise reiteratively during ontogeny and are characterized by stiff, slowly dividing cells that demarcate adjacent and divergent morphogenetic domains; the genetic mechanisms of cell fate acquisition within these boundaries are incompletely understood. Grass leaves are initiated at a developmental boundary in the periphery of the shoot apical meristem, an organogenic pool of plant stem cells that generates all lateral organs in the plant shoot. During later primordial growth, maize leaves form a de novo developmental boundary that ultimately separates the distal, photosynthetic leaf blade from the proximal, clasping leaf sheath. Morphogenesis at this blade/sheath boundary in maize leaves generates an epidermal outgrowth called the ligule and two tissue-wedges forming the auricle, a hinge-like structure with major effects on leaf angle, light capture, and yield. Here, we use cell lineage mapping, morphometric measures of cell division and expansion, cell-specific multidimensional transcriptomic analyses, and topological landscape modeling to investigate the mechanisms of cell fate acquisition at the ligule/auricle morphogenetic boundary in the maize leaf. The data suggest a model where auricle initial cells are recruited from blade founder cells at this boundary, via repression of blade identity during early stages in auricle ontogeny. Thereafter, auricle primordial cells assume a developmental genetic trajectory that is distinct from the blade, sheath, and ligule, thereby acquiring a unique auricle cell fate in the maize leaf.